Price and liquidity discovery in European sovereign bonds and futures - Ruggero Jappelli; Konrad Lucke; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2022)
This work uses financial markets connected by arbitrage relations to investigate the dynamics of price and liquidity discovery, which refer to the cross-instrument forecasting power for prices and liquidity, respectively. Specifically, we seek to understand the linkage between the cheapest to deliver bond and closest futures pairs by using high-frequency data on European governments obligations and derivatives. We split the 2019-2021 sample into three subperiods to appreciate changes in the liquidity discovery induced by the COVID-19 pandemic. Within a cointegration model, we find that price discovery occurs on the futures market, and document strong empirical support for liquidity spillovers both from the futures to the cash market as well as from the cash to the futures market.
Keywords: G12; G13; G15; 330; Fixed Income; Limits to Arbitrage; Market Liquidity